Development of the Tool for Evaluation of Quality of Mobile Data Services - Balciunas, D.; Batkauskas, V. (Elektronika ir Elektrotechnika, 2011)
Purpose of this paper is to analyze software tool created for the permanent monitoring of the mobile network QoS parameter andcollecting them at the end user premises. Therefore algorithms of the software tool functioning is described. The most importantparameters of the mobile data services - data transfer speed and delays are measured at the different environments. Results of themeasurements and their interpretations are presented. Parameterizations of the tool are described. Differences from the similar productsand advantages of the tool for the mobile operators and customers are presented. Ill. 6, bibl. 12, tabl. 1 (in English; abstracts in Englishand Lithuanian). http://dx.doi.org/10.5755/j01.eee.113.7.621